Development and validation of a high throughput LC–MS/MS method for simultaneous quantitation of pioglitazone and telmisartan in rat plasma and its application to a pharmacokinetic study - Sengupta, Pinaki; Chatterjee, Bappaditya; Mandal, Uttam Kumar; Gorain, Bapi; Pal, Tapan Kumar (Xi'an Jiaotong University, 2017)
Management of cardiovascular risk factors in diabetes demands special attention due to their co-existence. Pioglitazone (PIO) and telmisartan (TLM) combination can be beneficial in effective control of cardiovascular complication in diabetes. In this research, we developed and validated a high throughput LC–MS/MS method for simultaneous quantitation of PIO and TLM in rat plasma. This developed method is more sensitive and can quantitate the analytes in relatively shorter period of time compared to the previously reported methods for their individual quantification. Moreover, till date, there is no bioanalytical method available to simultaneously quantitate PIO and TLM in a single run. The method was validated according to the USFDA guidelines for bioanalytical method validation. A linear response of the analytes was observed over the range of 0.005–10 µg/mL with satisfactory precision and accuracy. Accuracy at four quality control levels was within 94.27%–106.10%. The intra- and inter-day precision ranged from 2.32% to 10.14% and 5.02% to 8.12%, respectively. The method was reproducible and sensitive enough to quantitate PIO and TLM in rat plasma samples of a preclinical pharmacokinetic study. Due to the potential of PIO-TLM combination to be therapeutically explored, this method is expected to have significant usefulness in future.